A concrete interface repair agent and its preparation method and application

By using a combination of sodium fluorosilicate and PSCA, the problem of poor bonding effect of existing interface repair agents on the interfaces of new and old concrete is solved, and efficient interface bonding and durability are achieved.

CN117361933BActive Publication Date: 2025-03-18GUANGDONG HIGHWAY CONSTR CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311365497.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-03-18
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

The existing interface repair agent has poor bonding effect on the interfaces of new and old concrete, resulting in a short service life of the repaired concrete and the problem that weak interface layer and CH crystals are not conducive to bonding.

Method used

A solution combination of sodium fluorosilicate and PSCA is used to generate stable crystals through the chemical reaction of sodium fluorosilicate and CH, harden the surface of the old concrete, and form a silane coupling layer through the coupling reaction of PSCA, improving the bonding performance of new and old concrete.

Benefits of technology

It significantly improves the bonding performance between the interfaces of new and old concrete, enhances the durability of repairing concrete, and reduces construction costs and operation difficulty.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of preparation of new and old concrete interface repair agents, and the present invention discloses an interface repair agent for concrete, a preparation method and an application thereof. The interface repair agent for concrete of the present invention comprises a solution of sodium fluorosilicate and a solution of PSCA; the solution of PSCA comprises potassium hydroxide, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and water. The present invention obtains repaired concrete by spraying a solution of sodium fluorosilicate and a solution of PSCA on the surface of the concrete to be repaired, respectively, and then repairing the concrete to be repaired. The repaired concrete has excellent bonding properties at the interface between new and old concrete, and the repaired concrete has excellent acid resistance, and the interface bonding properties of the concrete after acid corrosion can still reach a high level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of a new-old concrete interface repair agent, and in particular to an interface repair agent for concrete and a preparation method and application thereof. Background Art

[0002] As the world's most widely used building material, concrete consumption has surged with the rapid development of my country's economy, accounting for about 60% of the world's total. At the same time, as the service age increases, concrete structures inevitably suffer from cracks, erosion, large-scale surface shedding and even collapse due to human and natural factors, which seriously damages their safety and durability, causing direct economic losses of up to 300 billion yuan per year. Faced with the severe situation of the continuous deterioration of existing concrete structures, repair and reinforcement have become an effective solution.

[0003] At present, the commonly used interface repair agents are solvent-based epoxy resins or silane coupling agents. The molecular structure of silane coupling agents is generally an amphoteric structure, with a siloxane group at one end and a functional group at the other end. Silane alkoxy groups are reactive to inorganic substances, and after hydrolysis, they form silanol groups, which can chemically bond with the hydroxyl groups exposed on the inorganic surface. Functional groups such as amino, epoxy, vinyl, and thiol groups are all functional groups that are reactive or compatible with organic matter. Therefore, when the silane coupling agent is between the inorganic and organic interfaces, a bonding layer of organic matrix-silane coupling agent-inorganic matrix can be formed during the hydrolysis and condensation process. This feature can be used to construct chemical bonds on the cement-based and epoxy resin surfaces.

[0004] However, although such interface repair agents are chemically compatible and reactive with water-based epoxy-cement-based repair materials in theory, solvent-based epoxy resins and silane coupling agents are insoluble in water. After the repair material is poured, a layer of water film will still be formed between the interface repair agent layer, affecting the cross-linking of the new and old materials and causing the repair layer to debond. Therefore, when using conventional interface agents, the problem of bonding between the new and old interfaces still exists. In addition, existing interface repair agents have not yet solved the following problems based on the characteristics of the old concrete surface:

[0005] (1) After the concrete structure is damaged, the surface is cracked and loose. Even after grinding and roughening, a weak interface layer with low strength is sometimes formed on the bonding surface, resulting in repair failure or insufficient durability of the repaired structure;

[0006] (2) Concrete composite repair materials (NEPC) promote the growth of CH crystals. CH crystals have little effect on the bonding performance of the interface transition zone and are highly soluble. Once a large number of CH crystals are formed at the interface between new and old concrete, it is not conducive to the development of bonding strength. It is necessary to find a way to transform CH crystals into a stable state or a form that is beneficial to interface bonding.

[0007] (3) Silane coupling agent is not miscible with water and needs to be stirred continuously to promote the reaction and hydrolysis of siloxane end with water to form silanol group, so as to gradually increase the water solubility of coupling agent until it becomes a uniform aqueous solution. The hydrolysis and condensation of silane coupling agent requires the participation of water. If silane coupling agent is sprayed directly on the surface of old concrete, the reaction will be slow and the interface bonding efficiency will be low. If it is mixed with water and then sprayed, the balance of the mixing reaction of silane coupling agent and water needs to be solved. In addition, each silane coupling agent will form three molecules of methanol or ethanol after hydrolysis. The aggregation of these solvents at the interface is not conducive to cement hydration and will weaken the interface bonding force of waterborne epoxy-cement-based repair materials.

[0008] In addition to the above factors, the economic cost of repair, operability and construction efficiency should also be considered comprehensively. Therefore, the field urgently needs to develop a concrete interface repair agent that can effectively improve the bonding performance between water-based epoxy-cement-based repair materials and old concrete matrix and improve the durability of repaired concrete. Summary of the invention

[0009] The purpose of the present invention is to provide an interface repair agent for concrete and a preparation method and application thereof, so as to solve the problem that the existing interface repair agent has poor bonding effect on new and old concrete, resulting in a relatively low service life of the repaired concrete.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] The invention provides an interface repair agent for concrete, which comprises a sodium fluorosilicate solution and a PSCA solution; the PSCA solution comprises potassium hydroxide, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and water.

[0012] Preferably, the amounts of sodium fluorosilicate, potassium hydroxide and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane are: 1 to 20 parts of sodium fluorosilicate, 70 to 90 parts of potassium hydroxide, and 100 to 200 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0013] Preferably, the sodium fluorosilicate solution is an aqueous solution of sodium fluorosilicate; the mass concentration of the sodium fluorosilicate solution is 8-12%; and the mass concentration of the PSCA solution is 3-7%.

[0014] The present invention also provides a method for preparing the concrete interface repair agent, which is characterized by comprising the following steps:

[0015] Preparation of sodium fluorosilicate solution: Mix sodium fluorosilicate and water to obtain a sodium fluorosilicate solution;

[0016] Preparation of PSCA solution: Potassium hydroxide and water are mixed to obtain a mixed solution; N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise to the mixed solution and reacted twice to obtain a PSCA solution.

[0017] Preferably, when the potassium hydroxide and water are mixed, the mixing temperature is -25 to 2°C, and the mixing stirring rate is 400 to 600 r / min.

[0018] Preferably, the dropping temperature is -2 to 2°C, and the dropping rate is 0.8 to 1 mL / s.

[0019] Preferably, the two reactions include a first reaction and a second reaction.

[0020] Preferably, the temperature of the first reaction is -25 to 2°C, and the time of the first reaction is 5 to 7 hours; the temperature of the second reaction is -25 to 30°C, and the time of the second reaction is 10 to 14 hours; the stirring rates of the first reaction and the second reaction are independently 400 to 600 r / min.

[0021] The present invention also provides application of the interface repair agent for concrete prepared by the preparation method of the interface repair agent for concrete in concrete to be repaired.

[0022] Preferably, the method of application is as follows:

[0023] The sodium fluorosilicate solution is sprayed on the surface of the concrete to be repaired 1 to 3 times, and after the surface is dried, the PSCA solution is sprayed 2 to 4 times. After the concrete to be repaired is repaired and cured, repaired concrete is obtained.

[0024] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The concrete interface repair agent proposed in the present invention utilizes the complexation between the PSCA solution and the Na2SiF6 (sodium fluorosilicate) solution and the chemical reaction of Na2SiF6-CH to achieve hardening and roughening of the old concrete surface and improve the bonding performance between the new and old interfaces;

[0026] (2) The concrete interface repair agent proposed by the present invention has good operability and high construction efficiency, and low economic cost;

[0027] (3) The Na2SiF6 solution in the concrete interface repair agent proposed by the present invention has a hardening effect on the surface of the hardened cement paste. When there are loose, porous and other weak layers on the old concrete surface, Na2SiF6 can play a certain hardening and reinforcement role on the weak layer. Combined with the curing and sealing effect of PSCA at the interface, the bonding performance can be further improved.

[0028] (4) The synthesis method of the concrete interface repair agent proposed in the present invention is mature and simple in process, which can effectively improve the bonding performance between the water-based epoxy-cement-based repair material and the old concrete matrix, and is in line with the country's long-term development strategy. DETAILED DESCRIPTION

[0029] The invention provides an interface repair agent for concrete, which comprises a sodium fluorosilicate solution and a PSCA solution; the PSCA solution comprises potassium hydroxide, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and water.

[0030] In the present invention, the amounts of sodium fluorosilicate, potassium hydroxide and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane are: 1 to 20 parts of sodium fluorosilicate, 70 to 90 parts of potassium hydroxide, and 100 to 200 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane;

[0031] The amount of the sodium fluorosilicate used is preferably 8 to 15 parts, more preferably 10 to 12 parts; the amount of the potassium hydroxide used is preferably 80 to 85 parts, more preferably 82 to 84 parts; the amount of the N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane used is preferably 110 to 180 parts, more preferably 112 to 150 parts.

[0032] In the present invention, the sodium fluorosilicate solution is preferably an aqueous solution of sodium fluorosilicate; the mass concentration of the sodium fluorosilicate solution is preferably 8-12%, more preferably 9-10%; the mass concentration of the PSCA solution is preferably 3-7%, more preferably 4-6%.

[0033] The present invention also provides a method for preparing the concrete interface repair agent, which is characterized by comprising the following steps:

[0034] Preparation of sodium fluorosilicate solution: Mix sodium fluorosilicate and water to obtain a sodium fluorosilicate solution;

[0035] Preparation of PSCA solution: Potassium hydroxide and water are mixed to obtain a mixed solution; N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise to the mixed solution and reacted twice to obtain a PSCA solution.

[0036] In the mixing of potassium hydroxide and water of the present invention, the mixing is carried out in a coolant circulation pump, and the initial temperature of the mixing is preferably -25 to -15°C, more preferably -20 to -18°C; the final temperature of the mixing is preferably -2 to 2°C, more preferably 0 to 1°C; the stirring rate of the mixing is preferably 400 to 600 r / min, more preferably 500 to 550 r / min.

[0037] In the present invention, the dropping temperature is preferably -2 to 2°C, more preferably 0 to 1°C; the dropping rate is preferably 0.8 to 1 mL / s, more preferably 0.9 mL / s.

[0038] In the present invention, the two reactions include a first reaction and a second reaction; the first reaction is preferably carried out in a coolant circulation pump, and the second reaction is preferably carried out at room temperature.

[0039] In the present invention, the initial temperature of the first reaction is preferably -2 to 2°C, and more preferably 0 to 1°C; the final temperature of the first reaction is preferably -25 to -15°C, and more preferably -20 to -18°C; the time of the first reaction is preferably 5 to 7h, and more preferably 6 to 6.5h; the initial temperature of the second reaction is preferably -25 to -15°C, and more preferably -20 to -18°C; the final temperature of the second reaction is preferably 24 to 30°C, and more preferably 25 to 28°C; the time of the second reaction is preferably 10 to 14h, and more preferably 12 to 13h; the stirring rates of the first reaction and the second reaction are independently preferably 400 to 600r / min, and more preferably 500 to 550r / min.

[0040] In the present invention, after the second reaction is completed, the obtained solution is added dropwise to water to obtain a PSCA solution; the dropping rate is preferably 0.8 to 1 mL / s, and more preferably 0.9 mL / s.

[0041] In the mixed solution obtained by mixing potassium hydroxide and water according to the present invention, the mass volume ratio of potassium hydroxide to water is preferably 7-9 g:10 mL.

[0042] The concrete interface repair agent of the present invention utilizes sodium fluorosilicate to react with CH to generate stable crystals such as CaF2 and NaF, thereby hardening and roughening the surface of the old concrete and fixing the soluble Ca 2+ and Na + ; PSCA solution is sprayed on the surface of old concrete treated with sodium fluorosilicate solution, and the coupling reaction of PSCA is activated through the complexation of sodium fluorosilicate and PSCA, and sodium potassium fluoride crystals and silane coupling layers are instantly formed on the concrete surface; the cross-linking polymerization of amino groups of PSCA molecules with water-based epoxy and the condensation and ion complexation of active silanols with hydroxyl groups on the surface of old concrete are utilized to improve the bonding properties of new and old concrete, thereby providing a technical approach to solve the bonding problem between water-based epoxy-cement-based repair materials and old concrete substrates.

[0043] The synthesis method of the repair interface agent is mature and the process is simple. It can effectively improve the bonding performance between water-based epoxy-cement-based repair materials and old concrete matrix, which is in line with the country's long-term development strategy.

[0044] The present invention also provides application of the interface repair agent for concrete prepared by the preparation method of the interface repair agent for concrete in concrete to be repaired.

[0045] In the present invention, the method of application is as follows:

[0046] Spraying a sodium fluorosilicate solution on the surface of the concrete to be repaired 1 to 5 times, and after the surface is dried, spraying a PSCA solution 2 to 6 times, and repairing and curing the concrete to be repaired to obtain repaired concrete;

[0047] The number of spraying of the sodium fluorosilicate solution is preferably 2 to 4 times, more preferably 3 times; the number of spraying of the PSCA solution is preferably 3 to 5 times, more preferably 4 times; the surface drying is air drying;

[0048] The relative humidity of the curing is preferably ≥95%, more preferably ≥97%; the curing temperature is preferably 18-22°C, more preferably 19-20°C; the curing time is preferably 28-30 days, more preferably 29 days.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] The commercially available silane coupling agent used in the following examples is N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane with model number 1760-24-3 produced by Qingdao Kremer New Building Materials Technology Co., Ltd.; the N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane used is produced by Qingdao Kremer New Building Materials Technology Co., Ltd., with model number 1760-24-3; the commercially available solvent-based epoxy resin used is the self-emulsifying epoxy resin NEP produced by Qingdao Kremer New Building Materials Technology Co., Ltd.

[0051] Example 1

[0052] 10 g of sodium fluorosilicate and 100 mL of water were mixed to obtain a sodium fluorosilicate solution with a mass concentration of 10%;

[0053] In the coolant circulation pump, 84g of potassium hydroxide was dissolved in 100mL of water, and stirred at a rate of 500r / min at a temperature of -20°C. When the temperature dropped to 0°C, 112g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise at a rate of 0.8mL / s. The stirring rate was maintained at 500r / min during the addition. The reaction was stirred for 6h until the temperature reached -20°C. The coolant circulation pump was turned off, and the reaction was continued to be stirred at a rate of 500r / min at room temperature for 12h. The resulting solution was added to 900mL of water at a rate of 0.8mL / s to obtain a PSCA solution with a mass concentration of 5%.

[0054] Thirty identical concrete specimens to be repaired were divided into three groups, which were designated as specimens 1 to 3; the surface of specimen 1 to be repaired was sprayed with the obtained sodium fluorosilicate solution once, and after the surface was air-dried, the obtained PSCA solution was sprayed twice; the surface of specimen 2 to be repaired was sprayed with a commercially available silane coupling agent three times; the surface of specimen 3 to be repaired was sprayed with a commercially available solvent-based epoxy resin three times; after the spraying was completed, the same concrete was repaired on the surfaces of specimens 1 to 3 to be repaired, and the repaired concrete was placed in a curing box in an environment with a relative humidity of 96% and a temperature of 22°C for 28 days, and the interface bonding strength of the cured specimens 1 to 3 was tested.

[0055] After testing, the interface bonding strength of sample 2 after 28 days of curing was 2MPa, the interface bonding strength of sample 3 after 28 days of curing was 1.8MPa, and the interface bonding strength of sample 1 after 28 days of curing was 2.6MPa, which were 30% and 44.4% higher than those of sample 2 and sample 3 after curing, respectively.

[0056] The cured samples 1 to 3 were placed in a sulfuric acid solution with a mass concentration of 85% and aged for 90 days, and then their respective interface bonding strengths were measured.

[0057] After testing, the interface bonding strength of the cured sample 1 after aging was 1.1MPa, the interface bonding strength of the cured sample 2 after aging was 0.5MPa, and the interface bonding strength of the cured sample 3 after aging was 0.4MPa; and only two specimens of the cured sample 1 experienced interface debonding after aging, while four specimens of the cured samples 2 and 3 experienced interface debonding after aging.

[0058] Example 2

[0059] 8 g of sodium fluorosilicate and 100 mL of water were mixed to obtain a sodium fluorosilicate solution with a mass concentration of 8%;

[0060] In the coolant circulation pump, 84g of potassium hydroxide was dissolved in 100mL of water, and stirred at a rate of 500r / min at a temperature of -20°C. When the temperature dropped to 0°C, 112g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise at a rate of 0.8mL / s. The stirring rate was maintained at 500r / min during the addition. The reaction was stirred for 6h until the temperature reached -20°C. The coolant circulation pump was turned off, and the reaction was continued to be stirred at a rate of 500r / min at room temperature for 12h. The resulting solution was added to 900mL of water at a rate of 0.8mL / s to obtain a PSCA solution with a mass concentration of 5%.

[0061] Thirty identical concrete specimens to be repaired were divided into three groups, which were designated as specimens 1 to 3; the surface of specimen 1 to be repaired was sprayed with the obtained sodium fluorosilicate solution once, and after the surface was air-dried, the obtained PSCA solution was sprayed twice; the surface of specimen 2 to be repaired was sprayed with a commercially available silane coupling agent three times; the surface of specimen 3 to be repaired was sprayed with a commercially available solvent-based epoxy resin three times; after the spraying was completed, the same concrete was repaired on the surfaces of specimens 1 to 3 to be repaired, and the repaired concrete was placed in a curing box in an environment with a relative humidity of 96% and a temperature of 22°C for 28 days, and the interface bonding strength of the cured specimens 1 to 3 was tested.

[0062] After testing, the interface bonding strength of sample 2 after 28 days of curing was 2MPa, the interface bonding strength of sample 3 after 28 days of curing was 1.8MPa, and the interface bonding strength of sample 1 after 28 days of curing was 2.4MPa, which were 20% and 33.3% higher than those of sample 2 and sample 3 after curing, respectively.

[0063] The cured samples 1 to 3 were placed in a hydrochloric acid solution with a mass concentration of 10% and aged for 90 days, and then their respective interface bonding strengths were measured.

[0064] After testing, the interface bonding strength of the cured sample 1 after aging was 1MPa, the interface bonding strength of the cured sample 2 after aging was 0.5MPa, and the interface bonding strength of the cured sample 3 after aging was 0.4MPa; and only two specimens of the cured sample 1 experienced interface debonding after aging, while four specimens of the cured samples 2 and 3 experienced interface debonding after aging.

[0065] Example 3

[0066] 10 g of sodium fluorosilicate and 100 mL of water were mixed to obtain a sodium fluorosilicate solution with a mass concentration of 10%;

[0067] In the coolant circulation pump, 80g of potassium hydroxide was dissolved in 100mL of water, and stirred at a rate of 500r / min at a temperature of -20°C. When the temperature dropped to 0°C, 110g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise at a rate of 0.8mL / s. The stirring rate was maintained at 500r / min during the addition. The reaction was stirred for 6h until the temperature reached -20°C. The coolant circulation pump was turned off, and the reaction was continued to be stirred at a rate of 500r / min at room temperature for 12h. The resulting solution was added to 900mL of water at a rate of 0.8mL / s to obtain a PSCA solution with a mass concentration of 4.9%.

[0068] Thirty identical concrete specimens to be repaired were divided into three groups, which were designated as specimens 1 to 3; the surface of specimen 1 to be repaired was sprayed with the obtained sodium fluorosilicate solution once, and after the surface was air-dried, the obtained PSCA solution was sprayed twice; the surface of specimen 2 to be repaired was sprayed with a commercially available silane coupling agent three times; the surface of specimen 3 to be repaired was sprayed with a commercially available solvent-based epoxy resin three times; after the spraying was completed, the same concrete was repaired on the surfaces of specimens 1 to 3 to be repaired, and the repaired concrete was placed in a curing box in an environment with a relative humidity of 96% and a temperature of 22°C for 28 days, and the interface bonding strength of the cured specimens 1 to 3 was tested.

[0069] After testing, the interface bonding strength of sample 2 after 28 days of curing was 2MPa, the interface bonding strength of sample 3 after 28 days of curing was 1.8MPa, and the interface bonding strength of sample 1 after 28 days of curing was 2.3MPa, which were 15% and 27.8% higher than those of sample 2 and sample 3 after curing, respectively.

[0070] The cured samples 1 to 3 were placed in a hydrochloric acid solution with a mass concentration of 10% and aged for 90 days, and then their respective interface bonding strengths were measured.

[0071] After testing, the interface bonding strength of the cured sample 1 after aging was 0.9MPa, the interface bonding strength of the cured sample 2 after aging was 0.5MPa, and the interface bonding strength of the cured sample 3 after aging was 0.4MPa; and only two specimens of the cured sample 1 experienced interface debonding after aging, while four specimens of the cured samples 2 and 3 experienced interface debonding after aging.

[0072] Example 4

[0073] 10 g of sodium fluorosilicate and 100 mL of water were mixed to obtain a sodium fluorosilicate solution with a mass concentration of 10%;

[0074] In the coolant circulation pump, 84g of potassium hydroxide was dissolved in 100mL of water, and stirred at a rate of 500r / min at a temperature of -20°C. When the temperature dropped to 0°C, 110g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise at a rate of 0.8mL / s. The stirring rate was maintained at 500r / min during the addition. The reaction was stirred for 6h until the temperature reached -20°C. The coolant circulation pump was turned off, and the reaction was continued to be stirred at a rate of 500r / min for 12h at room temperature. The resulting solution was added to 900mL of water at a rate of 0.8mL / s to obtain a PSCA solution with a mass concentration of 4.9%.

[0075] Thirty identical concrete specimens to be repaired were divided into three groups, which were designated as specimens 1 to 3; the surface of specimen 1 to be repaired was sprayed with the obtained sodium fluorosilicate solution once, and after the surface was air-dried, the obtained PSCA solution was sprayed twice; the surface of specimen 2 to be repaired was sprayed with a commercially available silane coupling agent three times; the surface of specimen 3 to be repaired was sprayed with a commercially available solvent-based epoxy resin three times; after the spraying was completed, the same concrete was repaired on the surfaces of specimens 1 to 3 to be repaired, and the repaired concrete was placed in a curing box in an environment with a relative humidity of 96% and a temperature of 22°C for 28 days, and the interface bonding strength of the cured specimens 1 to 3 was tested.

[0076] After testing, the interface bonding strength of sample 2 after 28 days of curing was 2MPa, the interface bonding strength of sample 3 after 28 days of curing was 1.8MPa, and the interface bonding strength of sample 1 after 28 days of curing was 2.5MPa, which were 25% and 38.9% higher than those of sample 2 and sample 3 after curing, respectively.

[0077] The cured samples 1 to 3 were placed in a hydrochloric acid solution with a mass concentration of 10% and aged for 90 days, and then their respective interface bonding strengths were measured.

[0078] After testing, the interface bonding strength of the cured sample 1 after aging was 1MPa, the interface bonding strength of the cured sample 2 after aging was 0.5MPa, and the interface bonding strength of the cured sample 3 after aging was 0.4MPa; and only two specimens of the cured sample 1 experienced interface debonding after aging, while four specimens of the cured samples 2 and 3 experienced interface debonding after aging.

[0079] Example 5

[0080] 10 g of sodium fluorosilicate and 100 mL of water were mixed to obtain a sodium fluorosilicate solution with a mass concentration of 10%;

[0081] In the coolant circulation pump, 80g of potassium hydroxide was dissolved in 100mL of water, and stirred at a rate of 500r / min at a temperature of -20°C. When the temperature dropped to 0°C, 112g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane was added dropwise at a rate of 0.8mL / s. The stirring rate was maintained at 500r / min during the addition. The reaction was stirred for 6h until the temperature reached -20°C. The coolant circulation pump was turned off, and the reaction was continued to be stirred at a rate of 500r / min at room temperature for 12h. The resulting solution was added to 900mL of water at a rate of 0.8mL / s to obtain a PSCA solution with a mass concentration of 5%.

[0082] Thirty identical concrete specimens to be repaired were divided into three groups, which were designated as specimens 1 to 3; the surface of specimen 1 to be repaired was sprayed with the obtained sodium fluorosilicate solution once, and after the surface was air-dried, the obtained PSCA solution was sprayed twice; the surface of specimen 2 to be repaired was sprayed with a commercially available silane coupling agent three times; the surface of specimen 3 to be repaired was sprayed with a commercially available solvent-based epoxy resin three times; after the spraying was completed, the same concrete was repaired on the surfaces of specimens 1 to 3 to be repaired, and the repaired concrete was placed in a curing box in an environment with a relative humidity of 96% and a temperature of 22°C for 28 days, and the interface bonding strength of the cured specimens 1 to 3 was tested.

[0083] After testing, the interface bonding strength of sample 2 after 28 days of curing was 2MPa, the interface bonding strength of sample 3 after 28 days of curing was 1.8MPa, and the interface bonding strength of sample 1 after 28 days of curing was 2.4MPa, which were 20% and 33.3% higher than those of sample 2 and sample 3 after curing, respectively.

[0084] The cured samples 1 to 3 were placed in a hydrochloric acid solution with a mass concentration of 10% and aged for 90 days, and then their respective interface bonding strengths were measured.

[0085] After testing, the interface bonding strength of the cured sample 1 after aging was 1MPa, the interface bonding strength of the cured sample 2 after aging was 0.5MPa, and the interface bonding strength of the cured sample 3 after aging was 0.4MPa; and only two specimens of the cured sample 1 experienced interface debonding after aging, while four specimens of the cured samples 2 and 3 experienced interface debonding after aging.

[0086] It can be seen from Examples 1 to 5 that the interface repair agent for concrete obtained by the present invention can significantly improve the bonding performance between the new and old concrete interfaces, and the repaired concrete still has a relatively high bonding performance between the new and old concrete interfaces after acid leaching for 90 days.

[0087] The effect of the interface repair agent for concrete obtained by the present invention on cement hydration was tested, and the test method and results are as follows:

[0088] 10g cement (PO 52.5 ordinary Portland cement), 10mL sodium fluorosilicate solution obtained in Example 1, and 5mL PSCA solution obtained in Example 1 were mixed in 100mL water, and the curves of solution conductivity and temperature change with stirring time were measured. The results are as follows: the conductivity rose rapidly from 0μs / cm to 7300μs / cm within 10min, accompanied by a small amount of heat release, which was mainly due to the dissolution of soluble ions in cement particles. After adding the sodium fluorosilicate solution, the solution conductivity dropped rapidly to about 7100μs / cm within a few seconds and gradually stabilized at 6900μs / cm, accompanied by a large amount of heat release. After continuing to add the PSCA solution, the conductivity dropped to about 5300μs / cm within a few seconds, and gradually stabilized at 3600μs / cm within 40min. The reaction was accompanied by a small amount of stable heat release.

[0089] It can be seen from the above test results that the interface repair agent for concrete obtained by the present invention has little effect on cement hydration and also has little effect on the performance of concrete itself.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A concrete interface repair agent, characterized in that: The concrete interface repair agent is a solution of sodium fluorosilicate and a solution of PSCA; the PSCA solution is potassium hydroxide, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and water; The dosage of the sodium fluorosilicate, potassium hydroxide and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is: 1 to 20 parts of sodium fluorosilicate, 70 to 90 parts of potassium hydroxide, and 100 to 200 parts of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; The sodium fluorosilicate solution is an aqueous solution of sodium fluorosilicate; the mass concentration of the sodium fluorosilicate solution is 8-12%; the mass concentration of the PSCA solution is 3-7%.

2. The method for preparing the interface repair agent for concrete according to claim 1, characterized in that: The steps include: Preparation of sodium fluorosilicate solution: Mix sodium fluorosilicate and water to obtain a sodium fluorosilicate solution; Preparation of PSCA solution: Potassium hydroxide and water are mixed to obtain a mixed solution; N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane is added dropwise to the mixed solution and reacted twice to obtain a PSCA solution.

3. The method for preparing the interface repair agent for concrete according to claim 2, characterized in that: When the potassium hydroxide and water are mixed, the mixing temperature is -25 to 2° C., and the mixing stirring rate is 400 to 600 r / min.

4. The method for preparing the interface repair agent for concrete according to claim 2 or 3, characterized in that: The dropping temperature is -2 to 2°C, and the dropping rate is 0.8 to 1 mL / s.

5. The method for preparing the interface repair agent for concrete according to claim 4, characterized in that: The two reactions include a first reaction and a second reaction.

6. The method for preparing the interface repair agent for concrete according to claim 5, characterized in that: The temperature of the first reaction is -25 to 2°C, and the time of the first reaction is 5 to 7 hours; the temperature of the second reaction is -25 to 30°C, and the time of the second reaction is 10 to 14 hours; the stirring rates of the first reaction and the second reaction are independently 400 to 600 r / min.

7. Use of the interface repair agent for concrete prepared by the method for preparing the interface repair agent for concrete according to any one of claims 2 to 6 in concrete to be repaired.

8. The use of the concrete interface repair agent prepared by the preparation method of the concrete interface repair agent according to claim 7 in concrete to be repaired, characterized in that: The method of the application is as follows: The sodium fluorosilicate solution is sprayed on the surface of the concrete to be repaired 1 to 3 times, and after the surface is dried, the PSCA solution is sprayed 2 to 4 times. After the concrete to be repaired is repaired and cured, repaired concrete is obtained.

Citation Information

Patent Citations

  • Concrete curing agent, curing coating and preparation method thereof

    CN114478064A